How will integrator perceptions affect the adoption of radio frequency identification technology - Rodrigues, Mark J.; James, Kieran (2006)
Purpose - This study aims to assess the perceptions of leading Australian integrators within the RFID (radio frequency identification) Industry about the future of the industry and barriers to more widespread adoption of the technology.Methodology/approach - Five leading Australian integrators presently working within the RFID Industry were interviewed.Findings - We find that the interviewed managers were realistic and circumspect about the industry’s future and potential supply chain savings, which can be contrasted with the “hype” evident in the commercial literature (for example, AIMRFID Connections, 2003).Research implications - Understanding integrators’ current perceptions about the industry will help vendors and integrators to develop applications that will be more likely to gain widespread acceptance in the future.Originality/value - This paper provides a unique insight into the perceptions of leading Australian RFID suppliers and integrators regarding the future of the industry and barriers to more widespread adoption of the technology.